Kepemimpinan Kepala Sekolah dalam Mengatasi Konflik Antara Guru, Siswa, Dan Orang Tua - Eva Dewi Lestari; Siti Nur Inayah; Taufik Yunarta; Ruhil Amany; Viqi Noor Alfida (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The success of education depends not only on the quality of learning, but alsoon how conflicts that occur in the school environment can be managed properly.Conflicts between teachers, students, and parents often arise due to differencesin perceptions, expectations, or unmet needs. This article examines the role ofschool principals in addressing these conflicts with an effective leadershipapproach. Principals, as leaders in the educational community, are expected tohave the ability to create open communication and support collaborationbetween the various parties involved. Through an inclusive, adaptive, andproblem-solving-based leadership style, principals can identify sources ofconflict, defuse tensions, and create a harmonious environment. The approachesapplied include mediation, fostering interpersonal relationships, anddeveloping fair and transparent policies. The findings of this article suggest thateffective leadership of principals in dealing with conflict can improve thequality of interaction between teachers, students, and parents, which in turnsupports the creation of a more conducive and productive educational climate.